Prognostic value of baseline neutrophil/lymphocyte ratio in HER2-positive metastatic breast cancer: exploratory analysis of data from the CLEOPATRA trial - Nianhua Ding; Jian Pang; Xuan Liu; Xiongbin He; Wei Zhou; Haiqing Xie; Jianqi Feng; Guo Wang; Jie Tang; Jing Cao; Liying He; Yingjian He; et al. (Breast Cancer Research, 2024)
Abstract Purpose This study aimed to evaluate the prognostic role of the baseline neutrophil/lymphocyte ratio (NLR) in HER2-positive metastatic breast cancer (MBC) patients treated with trastuzumab/pertuzumab. Experimental design Data from 780 patients from the CLEOPATRA trial and 248 local patients were collected. Patients were divided into the low and high NLR subgroups by the NLR cutoff value. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) methods were used to control bias. Associations between the NLR and progression-free survival (PFS) and overall survival (OS) were analyzed. Results The baseline characteristics of the subgroups were well balanced after PSM and IPTW. A low baseline NLR was associated with better PFS and OS in the trastuzumab and docetaxel (TH) group in the unadjusted, PSM and IPTW models. After IPTW, a low NLR, versus a high NLR, was associated with improved PFS (HR 1.35, 95% CI 1.07–1.70, P = 0.012) and OS (HR 1.47, 95% CI 1.12–1.94, P = 0.006) in the TH group. In patients undergoing treatment with trastuzumab and pertuzumab and docetaxel (THP), a low baseline NLR was also correlated with better PFS but not OS across the three models. After IPTW, a low NLR was associated with better PFS (HR 1.52, 95% CI 1.20–1.93, P = 0.001) than a high NLR in the THP group. Multivariate analyses showed that a low baseline NLR was a predictor for PFS and OS in the TH group and for PFS in the THP group in all three models. In the real-world setting, a low baseline NLR was a predictor of better PFS among patients treated with docetaxel plus trastuzumab without or with pertuzumab in the multivariate model (P = 0.015 and 0.008, respectively). Conclusions A low baseline NLR is associated with better survival outcomes among HER2-positive MBC patients receiving docetaxel plus trastuzumab/pertuzumab as first-line therapy.